2015
DOI: 10.1007/s10295-014-1554-9
|View full text |Cite
|
Sign up to set email alerts
|

Applications of genome-scale metabolic network model in metabolic engineering

Abstract: Genome-scale metabolic network model (GEM) is a fundamental framework in systems metabolic engineering. GEM is built upon extensive experimental data and literature information on gene annotation and function, metabolites and enzymes so that it contains all known metabolic reactions within an organism. Constraint-based analysis of GEM enables the identification of phenotypic properties of an organism and hypothesis-driven engineering of cellular functions to achieve objectives. Along with the advances in omics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 96 publications
(134 reference statements)
0
54
0
Order By: Relevance
“…The existing body of work evaluating different E. coli strains in metabolic engineering and synthetic biology (Archer et al, 2011, Arifin et al, 2014, Yoon et al, 2012, Vijayendran et al, 2007, Marisch et al, 2013, Chae et al, 2010) demonstrated a need for the comprehensive analysis of strain-specific differences. Despite significant success in engineering E. coli for industrial production of chemicals and proteins (Lee et al, 2012b, Kim et al, 2015), there is no unified fundamental basis for selection of one strain over another for a given metabolic engineering project or expression of a given construct. Previous studies have shown that the choice of host strain for production of a given compound has a significant impact on results (Na et al, 2013, Kim et al, 2014) and up until now represented a major brute force screening effort.…”
Section: Introductionmentioning
confidence: 99%
“…The existing body of work evaluating different E. coli strains in metabolic engineering and synthetic biology (Archer et al, 2011, Arifin et al, 2014, Yoon et al, 2012, Vijayendran et al, 2007, Marisch et al, 2013, Chae et al, 2010) demonstrated a need for the comprehensive analysis of strain-specific differences. Despite significant success in engineering E. coli for industrial production of chemicals and proteins (Lee et al, 2012b, Kim et al, 2015), there is no unified fundamental basis for selection of one strain over another for a given metabolic engineering project or expression of a given construct. Previous studies have shown that the choice of host strain for production of a given compound has a significant impact on results (Na et al, 2013, Kim et al, 2014) and up until now represented a major brute force screening effort.…”
Section: Introductionmentioning
confidence: 99%
“…It can help to identify targets that couple cell growth with product formation, e.g., targets for gene upregulation, downregulation, and gene deletion 34, 35 . In IMGMD, a library that combines in vivo and in silico results to guide metabolic engineering was created.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some stoichiometric models covering the full genome have been used to design microbial cell factories [53,54]. In this case thermodynamic constraints have played an important role narrowing the number of feasible pathways [55][56][57][58].…”
Section: Applying Thermodynamic Pathway Analysis In Strain Designmentioning
confidence: 99%